Spatial assessment of coastal flood risk due to sea level rise in China’s coastal zone through the 21st century - Xu, He; Hou, Xiyong; Li, Dong; Wang, Xiaoli; Fan, Chao; Du, Peipei; Song, Baiyuan (Frontiers in Marine Science, 2022)
Among the climate change-induced threats to coastal regions, coastal flooding caused by sea level rise (SLR) is considered one of the most serious and presents an intensifying trend over time. The negative impacts and risks associated with coastal flooding are difficult to visualize spatially and cause great inconvenience to policy-makers in understanding the distribution of different risk levels and developing adaptation policies. Our study proposes a framework for coastal flood risk (CFR) based on the hazard, exposure & sensitivity, and adaptive capacity of China’s coastal zone (CCZ) and maps the spatial distribution of CFR by GIS in 2030, 2050, and 2100 under RCP2.6-SSP1, RCP4.5-SSP2, and RCP8.5-SSP5, respectively. Our results reveal that (1) low-lying coastal areas with densely populated, economically developed, or industrially diverse are faced with serious CFRs, such as the Yellow River Delta, the Yangtze River Delta, the Pearl River Delta, and the coastal areas in Jiangsu. (2) The area of “Very high” CFR level in the CCZ reaches a peak of 44.10×103 km2 in 2100 under RCP8.5-SSP5. And under the higher emission scenario, the areas of five CFR levels would change dramatically in the future. (3) The coastal area of Guangdong is significantly faced with the massive expected population and GDP affected due to CFR among scenarios and years. (4) As threatened by CFR mostly, built-up and farmland are particularly required to guard against the negative impact of coastal flooding, especially in Guangdong and Jiangsu. Results in this study are expected to provide the intuitive information and basis for governments, policy-makers, and local communities in addressing the increased CFR over the CCZ. Besides, our framework of CFR and methodology are flexible and can be adapted for other countries facing the threat of SLR.